Stride toward freedom : the Montgomery story. - King, Martin Luther, Jr., 1929-1968. (New York : Harper, 1958)
Chronicles the Montgomery, Alabama bus boycott sparked by Mrs. Rosa Park's refusal to give up her seat to a white male, describing the plans and problems of a nonviolent campaign, reprisals by the white community, and the eventual attainment of desegrated city bus service.
Keywords: Montgomery Bus Boycott, Montgomery, Ala., 1955-1956.; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century; African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century; Civil rights movements -- Alabama -- Montgomery -- History -- 20th century; Montgomery Bus Boycott, Montgomery, Ala., 1955-1956.; Segregation in transportation; African Americans -- Civil rights; Race relations; Montgomery (Ala.) -- Race relations